TOPONYMS AND THEIR ROLE IN LINGUISTICS - Sadriddinova Hulkarkhan Zafarjan's daughter (Web of Journals Publishing, 2025)
This article examines the role of toponyms in linguistics, their origin, structural features, and their relationship with other areas of linguistics. Linguistic analysis of toponyms serves to reveal their historical, geographical and cultural content. Their relationship with regional dialectology, semantics and lexicography is also analyzed.
Keywords: Toponym, linguistics, geographical names, semantics, etymology, cultural heritage.